How COVID-19 affected participation in ultramarathons: gender, risk aversion, and travel - Cary, M.; Stephens, H. M. (Journal of Sports Economics, 2025)
In this article, we study runners` decisions to compete in an ultramarathon during the COVID-19 era. To do this, we use a novel data set containing information on ultramarathon races and their participants and a logit model to determine if a runner who competed in an event in the year before the pandemic began chose to compete in that same (or sufficiently similar) event during the first year of the pandemic. By doing this we are able to estimate the impact of local and race destination COVID-19 cases on the decision to compete. We find that local COVID-19 cases, but not destination COVID-19 cases, affect the decision to compete. We also find that events were more likely to be cancelled when COVID-19 cases rose in the state in which the race is located. It also appears that women were disproportionately affected by the pandemic regarding changes in travel behavior.